Ohranjanje delovne zmožnosti - izziv za rehabilitacijo v prihodnosti - Fatur-Videtič, Andrejka (Rehabilitacija (Ljubljana), 2009)
The article discusses the changes in demographic, health and disability statistics of the Slovenian population. They are defined as a challenge for rehabilitation in the future - the achieved level of work ability and return to work should be included among the outcome measures of health and rehabilitation treatment. In that manner rehabilitation should contribute to the disability management strategy. The role of bio-psycho-social model for the defenition of work ability is stressed. The article includes an outline of selected literature to illustrate future development directions for rehabilitation and vocational rehabilitation through rehabilitation programs which seem to have possible positive contribution to return to work and employment of working-age patients and clients.
Keywords: delovna zmožnost; rehabilitacija; vocational rehabilitation; poklicna rehabilitacija